Efficacy and safety analysis in metastatic cancer patients treated with multiple courses of repeat radiation therapy - Maiwand Ahmadsei; Sebastian M. Christ; Tiuri E. Kroese; Anja Kühnis; Jonas Willmann; Panagiotis Balermpas; Nicolaus Andratschke; Stephanie Tanadini-Lang; Matthias Guckenberger (Clinical and Translational Radiation Oncology, 2023)
Background and purpose: Due to advances in oncology, a growing proportion of patients is treated with repetitive courses of radiotherapy. The aim of this study is to analyze whether radiotherapy maintains its safety and efficacy profile in patients treated with multiple repeat courses of irradiation. Material and methods: All patients treated between 2011 and 2019 at our institution were screened for a minimum of five repeat irradiation courses, to analyze treatment characteristics, survival, safety and efficacy. The type of re-irradiation was classified according to ESTRO-EORTC consensus guidelines. Results: A total of n = 112 patients receiving n = 660 radiotherapy courses were included in this retrospective cohort study. The most frequent primary tumors were lung cancer in 41.9 % (n = 47) and malignant melanoma in 8.9 % (n = 10). The most frequent re-irradiation types were repeat irradiation and Type 2 re-irradiation in 309 (46.8 %) and 113 (17.1 %) cases, respectively. Median survival after the first course of radiotherapy was 3.6 (0.3–13.4) years. Response to radiotherapy was observed in 548 (83.0 %) cases and CTCAE toxicity grade ≥ 3 was observed in 21 (3.2 %) cases. An increasing number of RT courses (HR: 1.30, p=<0.0001), Type 1 re-irradiation (HR 3.50, p = 0.008) and KPS ≤ 80 % (HR: 2.02, p = 0.002) were associated with significantly worse treatment responses. Toxicity rates remained stable with increasing numbers of RT courses. Conclusion: Multiple courses of repeat radiotherapy maintain a favorable therapeutic ratio of high response combined with reasonable safety profile.